Zredukuj wyrazy podobne :
a) b+ a +r + b + a + p + a + p + a
b)b-a-r-b-a-p-a-p-a
c)a + 2b + 3c - 4c - 5b - 6a
d) a³ + 2a + a² + 3a²- 10 a³ + 5
e) 5x² - x² + y² + y - 3 - y + ( -2)y² + 5
f) 13x + 7y - 10x - 4y + 5y
g) 90x + 3y -x² - 9 *9x - 2y + x²

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T14:08:43+01:00
A) b+ a +r + b + a + p + a + p + a=4a+2b+2p+r
b)b-a-r-b-a-p-a-p-a=-4a-2p-r
c)a + 2b + 3c - 4c - 5b - 6a=-5a-3b-c
d) a³ + 2a + a² + 3a²- 10 a³ + 5=-9a³+4a²+5
e) 5x² - x² + y² + y - 3 - y + ( -2)y² + 5=4x²-y²+2
f) 13x + 7y - 10x - 4y + 5y=3x+8y
g) 90x + 3y -x² - 9 *9x - 2y + x²=181x+y
111 4 111
2010-02-07T14:17:48+01:00
A)4a+2b+2p+r
b)4a-2p-r
c)-5a-3b-c
d)2a-9a³+4a²+5
e)4x²-y²+2
f)3x+8y
g)181x+y
52 4 52